A quadratic equation works like this.
x+10=0 or x-2=0
x=-10 or x=2
So when you are given the zeroes, just work backwards. For example if your zeroes, or roots, are 5 and -3, that means
x=5 or x = -3 which comes from
x-5=0 or x+3=0 which comes from
(x-5)(x+3)=0 which multiplied out, which is what I think you're refering to when you say the box method, is
The same thing happens in a cubic equation or any other power for that matter.
your zeroes are -2, 3, -5 which means
x+2=0, x-3=0, or x+5=0 which comes from
(x+2)(x-3)(x+5)=0 so multiply that out to get
(x2-x-6)(x+5)=0 which equals
Again, I'm not sure what the box method is but your final answeer should match up with mine.
Hope this helped.